Long-Term Responses to Large Minimum Wage Shocks: Sub-Minimum and Super-Minimum Workers in Slovenia - Suzana Laporsek; Peter F. Orazem; Matija Vodopivec; Milan Vodopivec (Institute of Labor Economics (IZA), 2019)
This study examines long-term effects of a minimum wage increase using an innovative identification strategy based on categorising workers according to their predicted marginal revenue products. It finds that the increase had a large and persistent disemployment effects on low-paid workers and that it triggered substitution toward more productive workers. As a consequence, the sub-minimum workers as a group lost average earnings, hours and employment compared to other workers. The adverse employment effect occurred both through a higher probability of transition from employment to non-employment and through a decreased probability of transition from non-employment to employment.
Keywords: J38; J31; 330; minimum wage; employment; unemployment; hours; earnings; Slovenia